السرد المضاد والمقاومة الثقافية، قراءة تأويلية في المجموعة القصصية "تقاسيم الفلسطيني" لسناء شعلان - قادري, آسيا; بارة, عبد الغني (جامعة الوادي - University of Eloued, 2020)
ملخص: استعاد السرد القصصي الواقع المأساوي الفلسطيني وأعاد تمثيله لغة وتخييلا، تمثيلا يبرز دوره في المقاومة الثقافية من خلال المجموعة القصصية "تقاسيم الفلسطيني" للمبدعة سناء شعلان، ليقول السرد المأساة الفلسطينية بكثير من التفاصيل النصيّة التي تصدم القارئ، وتربك فيه محدوديّة معرفته المكتسبة عمّا يجري في فلسطين من محو وإلغاء ومأساة إنسانية....، يحياها الفلسطيني في واقعه المعاش اليومي، ليعيد القارئ صياغة تصورات جديدة عن العلاقة بين الآخر الصهيوني، والذات الفلسطينية المجروحة، مبنيّة على تجربة سرديّة مضادّة لفعل تشويه حقيقة ما يجري في فلسطين. من أجل الوصول إلى هكذا نتيجة، فإن السرد المضاد أو الردّ بالكتابة مثلما اصطلح عليه بيل أشكروفت، يبرز كمنجز إبداعي يستدعي قارئا متفاعلا، تفاعلا يكشف به عن الفضاء الماثل في "تقاسيم الفلسطيني" وهو فضاء يتخذ لنفسه وضعيات سردية نصيّة تتمثل في "تقاسيم المعتقل، تقاسيم الوطن، تقاسيم المخيم، تقاسيم الشتات، تقاسيم العرب، تقاسيم العدو، تقاسيم البعث"، تحكي عن وطن مجروح تحت الظلم والمجازر...، وحين يقترن النص القصصي بهذا الفضاء الأكبر، ويجاري ما يحدث في الواقع الفلسطيني يتحول إلى ردّة فعل سرديّة تدرك وفق سياق أوسع هو سياق التلقي، تتحقق فيه مقاومته النصيّة قراءة وتأويلا؛ فبين الانجاز والتلقي يأتي التأويل كرؤية منهجية نصية تسعى إلى استظهار دور السرد المضاد في بعث وإحياء المقاومة الثقافية ضد اغتصاب الإنسانية في فلسطين. الكلمات المفاتيح: المأساة الفلسطينية، فعل القراءة، التأويل، السرد المضاد، المقاومة الثقافية. Abstract: The narrative recounted the Palestinian tragic reality and re-represented it both in language and illusion, a representation whose role in cultural resistance is reflected in the narrative series "Features of the Palestinian" by Sana Shaalan. The narration reveals the Palestinian tragedy in many textual details that shock the reader, and confuse his/her limited acquired knowledge of what is happening in Palestine, from eradication, elimination and human tragedy ... daily lived by the Palestinian, so as to let the reader reformulate new perceptions of the relationship between the Zionist Other, and the hurt Palestinian, being based on an anti-narrative experience that encounters the distorted reality of what is going on in Palestine. In order to reach such a result, the counter-narration or response in writing, as Bill Ashcroft called it, stands out as a creative realization that calls for an interactive reader, in an interaction that exposes the present space in the " Takassim El Falesstini ". It’s a space that adopts many narrative textual positions , like : « the features of the homeland, the features of the camp, the features of the diaspora, the features of the Arabs, the features of the enemy, the features of the Baath " ; all these tell about an injured homeland that is under oppression and massacres ... When the narrative text is associated with such a larger space, keeping up with what happens in Palestinian reality, it turns into a narrative reaction, that is perceived through a broader context , which is the reception, in which its textual resistance is realized both in reading and interpretation. Hence, between achievement and reception comes the interpretation as a methodical textual vision, seeking to memorize the role of counter narratives in the revival of cultural resistance against the rape of humanity in Palestine. key words: The Palestinian tragedy, the act of reading, interpretation, counter narration, cultural resistance.
مقال
Keywords: المأساة الفلسطينية، فعل القراءة، التأويل، السرد المضاد، المقاومة الثقافية; key words: The Palestinian tragedy, the act of reading, interpretation, counter narration, cultural resistance